Pedagogical Test For Schoolchildren And Its Features - Khilola Kamalova (The American Journal of Social Science and Education Innovations, 2021)
This article deals with the use of test methods at various study years, advantages and disadvantages of them, as well as individual approach to testing and orientation according to the criteria of limited meaning selection.